Breast Reconstruction after Mastectomy - Schmauss, Daniel; Machens, Hans-Günther; Harder, Yves (Frontiers in Surgery, 2016)
Breast cancer is the leading cause of cancer death in women worldwide. Its surgical approach has become less and less mutilating in the last decades. However, the overall number of breast reconstructions has significantly increased lately. Nowadays breast reconstruction should be individualized at its best, first of all taking into consideration oncological aspects of the tumor, neo-/adjuvant treatment and genetic predisposition, but also its timing (immediate versus delayed breast reconstruction), as well as the patient’s condition and wish. This article gives an overview over the various possibilities of breast reconstruction, including implant- and expander-based reconstruction, flap-based reconstruction (vascularized autologous tissue), the combination of implant and flap, reconstruction using non-vascularized autologous fat, as well as refinement surgery after breast reconstruction.